1997
DOI: 10.1007/s001150050115
|View full text |Cite
|
Sign up to set email alerts
|

Validität der Erfassung schizophrener Basissymptome

Abstract: A study on the concept and measurement of the basic disorders of schizophrenia is presented. A total of 151 male adult psychiatric inpatients (51 with a dual diagnosis of schizophrenia and alcoholism, 50 schizophrenics and 50 alcoholics) were included. The aims of this study were: (1) the replication of the previous finding that the Frankfurt Complaint Questionnaire (FBF) contains items that discriminate between schizophrenia and alcoholism; (2) an empirical comparison between FBF and the Bonn Scale for the As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…Although the reliability of self-reported measurements largely depends on the individuals' insight into their own experiences, a selfreport format still has its own advantage of being able to assess the , 2016). Lacking this assurance, questionnaireassessed basic symptoms have consistently been reported to correspond to their interview-assessed counterparts poorly (Maß et al, 1997;Michel, Kutschal et al, 2017). Furthermore, since the selection of basic symptoms in the basic symptom criteria and the FCQ-S greatly differ, respectively, this may further limit the comparability of our results with early detection studies on basic symptoms.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Although the reliability of self-reported measurements largely depends on the individuals' insight into their own experiences, a selfreport format still has its own advantage of being able to assess the , 2016). Lacking this assurance, questionnaireassessed basic symptoms have consistently been reported to correspond to their interview-assessed counterparts poorly (Maß et al, 1997;Michel, Kutschal et al, 2017). Furthermore, since the selection of basic symptoms in the basic symptom criteria and the FCQ-S greatly differ, respectively, this may further limit the comparability of our results with early detection studies on basic symptoms.…”
Section: Discussionmentioning
confidence: 81%
“…Today, basic symptoms are commonly assessed in clinical interviews using the Schizophrenia Proneness Instruments (Schultze‐Lutter, Addington, Ruhrmann, & Klosterkötter, ; Schultze‐Lutter & Koch, ) or in self‐ratings using the Frankfurt Complaint Questionnaire (Süllwold, ). However, albeit originally developed in close collaboration, studies on convergent validity reported extremely poor correspondence between interview‐ and questionnaire‐assessed basic symptoms (Maß, Hitschfeld, Wall, & Wagner, ; Michel, Kutschal, Schimmelmann, & Schultze‐Lutter, ). There has been increasing evidence to show that the combination of schizotypy and/or basic symptoms and UHR criteria, improve the accuracy of predicting the development of schizophrenia spectrum psychosis in help‐seeking individuals (Flückiger et al, ; Ruhrmann et al, ; Schultze‐Lutter, Klosterkötter, & Ruhrmann, ).…”
Section: Introductionmentioning
confidence: 99%
“…Investigaciones realizadas con éste y otros cuestionarios autoadministrados, demuestran que tienden a sobrevalorar los síntomas en las poblaciones estudiadas (89)(90)(91).…”
Section: Rev Neuropsiquiatr 80 (1) 2017unclassified
“…One is based on the basic symptoms concept, which was developed in Germany during the late 1960s and early 1970s (Huber, 1966;Huber et al 1975), and led to the development of the Bonn Scale for the Assessment of Basic Symptoms (Maß et al 1997) and the Frankfurter Beschwerde Fragebogen (Süllwold, 1991). To acquire information on every patient, besides history, specific standardised rating scales are needed.…”
Section: Introductionmentioning
confidence: 99%